'Hooligans, spivs and loafers'? : the politics of vagrancy in 1960s southern Rhodesia - Alexander, J (Cambridge University Press, 2012)
In 1960, amidst the most violent period of protest since conquest, the Southern Rhodesian government implemented a new Vagrancy Act alongside a range of repressive legislation. The Act's origins lay in a particular analysis of the social origins of unrest. It was unprecedented in promising not to exclude and criminalise ‘vagrants’ but to rehabilitate them as productive urban citizens. By presenting the Act as reformist and progressive, the government sought legitimacy for its actions. In fact, the Vagrancy Act was deeply punitive, underlining the tensions between reform and repression in settler social engineering. African leaders and Africans targeted by the Act saw it as a means of humiliating and criminalising those denied a livelihood by the settler political economy. In rejecting the Act, they invoked different models of citizenship to those on offer from the state. The Vagrancy Act ultimately met its demise at the hands of the Rhodesian Front, whose analysis of African protest made no space for the possibilities of reformist social engineering.